Interaction between APOE4 and lifestyle on neuroimaging biomarkers and cognition in cognitively unimpaired older adults. (20th December 2022) - Felisatti, Francesca; Chauveau, Léa; de Flores, Robin; Marchant, Natalie L; Collette, Fabienne; Demnitz‐King, Harriet; Whitfield, Tim; Requier, Florence; Palix, Cassandre; Haudry, Sacha; Delarue, Marion; la Sayette, Vincent De; et al.
Abstract: Background: APOE4 is the main genetic risk factor for Alzheimer's disease (AD). Recent findings suggest that lifestyle factors could modulate the association between APOE4 and cognitive impairment and/or dementia risk. However, a comprehensive assessment of the interactions between lifestyle and APOE4 status on neuroimaging and cognitive markers of aging and AD is still missing. Our objective is to assess this question in cognitively normal elderly. Method: Baseline data of 134 cognitively unimpaired older adults (mean age: 69) from the Age‐Well study were analysed. They underwent lifestyle questionnaires (physical and cognitive activity, and diet), neuropsychological assessment (global cognition, memory, attention and executive functions) and multimodal neuroimaging (structural MRI, FDG‐ and Florbetapir‐PET). Interactions between lifestyle and APOE4 status on neuroimaging and cognition were assessed for each lifestyle factor separately. Result: There was an interaction between APOE4 status and cognitive activity on neuroimaging measures (p‐values<.04), such that higher cognitive engagement was associated with lower grey matter volume in the parahippocampal cortex and lower brain perfusion in the entorhinal and perirhinal cortices in APOE4 carriers only (Figure 1A). However, greater cognitive engagement was associated with increased cognitive performance (global cognition, executive function and attention, all p‐values<.005), and this irrespective of APOE4 status (i.e., no cognitive activity x APOE4 status interaction; Figure 1B). For diet, interactions were evidenced (p‐values <.04) such that higher adherence to the Mediterranean diet was associated with i) higher brain glucose metabolism in the medial temporal lobe (Figure 2A) and ii) higher performance on attention tests (Figure 2B) in APOE4 carriers only. No interactions were found for physical activity. Conclusion: Our results indicate that APOE4 carriers with higher cognitive activity had lower brain outcomes but preserved cognition, suggesting that enriched cognitive engagement promotes cognitive resilience in this population. On the other hand, APOE4 carriers with higher adherence to the Mediterranean diet had greater cerebral metabolism and greater attention capacities. Overall, this suggests that distinct lifestyle factors differentially help APOE4 carriers to resist or cope with brain alteration and postpone cognitive decline. ClinicalTrials.gov Identifier: NCT02977819.